Elevating Repositioning Costs - Menon, Anoop R.; Yao, Dennis A. (Strategic Management Journal, 2017)
[Research summary: This article proposes an approach for modeling competitive interactions that incorporates the costs to firms of changing strategy. The costs associated with strategy modifications, which we term “repositioning costs,” are particularly relevant to competitive interactions involving major changes to business strategies. Repositioning costs can critically affect competitive dynamics and, consequently, the implications of strategic interaction for strategic choice. While the literature broadly recognizes the importance of such costs, game-theoretic treatments of major strategic change, with very limited exceptions, have not addressed them meaningfully. We advocate greater recognition of repositioning costs and illustrate with two simple models how repositioning costsmay facilitate differentiation and affect the value of a firm’s capability to reduce repositioning costs through investments in flexibility. Managerial summary:This article illustrates how the decision to make a strategic change is affected by both the cost to the firm of making the various strategy modifications, as well as the cost to its rivals of changing their strategies in response. These “repositioning costs” are important because they shape the responses each competitor would likely make to a move by the other competitor, and should be anticipated when considering an initial change to one’s own strategy. The paper shows how repositioning costs can be used strategically to facilitate differentiation, and to assess the value of potential investments in flexibility.]